The coronavirus advancement and the challenges for health care in vulnerable communities in the interior of Pernambuco State, Brazil (Research, Society and Development, 2020)
The provision of an efficient health system in the prevention, diagnosis and treatment of infections in public emergencies, such as the COVID-19 pandemic, in regions of Brazil with limited resources is a challenging task, especially in vulnerable communities. The objective of the present study was to systematize aspects about the transmission and contagion of the coronavirus, and its implications for physical health and the treatment of groups considered at risk, such as the elderly and the chronically ill, the poorest people and traditional communities, within Pernambuco. Finally, impacts on mental health and work were addressed in the context of this fragility during the pandemic. Vulnerable populations are especially more susceptible to new coronavirus due to immunodeficiency, more collective traditional ways of life, with little access to health services and hospitals. Absence of effective public policies, lack of SUS resources, fear of contagion, social isolation, lack of information and treatment, mourning and loss of people are the main problems faced by this portion of the population.